Anti-hyperglycemic effect of herbal formula of Moringa oleifera, Vernonia amygdalina and Centella asiatica extracts in streptozotocin-induced hyperglycemic mice - Thi Thanh Loan Tran; Hai Trieu Ly; Thi Kim Oanh Le; Van Minh Le (Elsevier, 2024)
Introduction: Moringa oleifera, Vernonia amygdalina, and Centella asiatica are herbs used in traditional Chinese medicine and are commonly used in Southeast Asian countries to treat a variety of diseases. The experimental evidence showed that M. oleifera leaves, V. amygdalina leaves, and C. asiatica had the effect of supporting their treatment of diabetes. This study investigated the anti-hyperglycemic effect of a novel herbal formula from M. oleifera leaf, V. amygdalina leaf, and C. asiatica aerial part extracts. Methods: The extract was examined for anti-hyperglycemic capacity in oral glucose tolerance test in normal mice. To confirm their role in a higher model, the extract was studied in the streptozotocin (STZ)-induced hyperglycemic model. Plasma glucose concentration, body weight, organ weight, malondialdehyde, glutathione in liver and kidneys, and pancreatic histology were also evaluated. Besides, in vitro properties of the extract were tested including α-amylase and α-glucosidase inhibitory, and antioxidant activities. Results: After 7-day of treatment, the extract showed strong anti-hyperglycemic activity in the STZ-induced hyperglycemic mice, plasma glucose levels were reduced by 48.75 % and 54.13 % in the group administered with 200 mg/kg and 400 mg/kg of the extract, respectively, compared with the hyperglycemic control. The extract had the effect to protect the liver and kidneys against oxidation stress by enhancing glutathione levels in the liver and decreasing malondialdehyde levels in the liver and kidneys. The pancreatic β-cell protection was also observed by improving the size and number of pancreatic islets by the extract compared to the hyperglycemic control. The extract showed a significant α-amylase and α-glucosidase inhibitory activities, and antioxidant activity through DPPH and ABTS quenching and reducing power abilities. Discussion: These results demonstrated remarkable potential of the combined extract of M. oleifera leaves, V. amygdalina leaves, and aerial part of C. asiatica in the management of diabetes.